Optimizing Damar Kurung Culture as an Integrative Thematic Learning Media Based on Gender Education - Fitria Larasati; Khakam Ma’ruf (International Journal of Scientific Multidisciplinary Research, 2023)
This research is oriented towards presenting the process of optimizing the application of gender education-based integrative thematic learning media using damar kurung culture. This research refers to literature study and data analysis conducted at SMP Muhammadiyah 6 Manisrenggo. The results obtained are that the integrative thematic learning model has not been applied optimally, even though it should have been implemented in schools that implement the 2013 curriculum. Damar kurung with the theme of gender education is one of the options for utilizing integrative thematic learning media. This research can provide benefits to the next generation in increasing their insight and awareness regarding the existence of local learning media potential with damar kurung media innovation. Damar kurung can also be utilized as a source of information and reference regarding integrative thematic learning media based on gender education. Damar kurung as a cultural wealth in Indonesia should continue to be preserved by the next generation of the nation, namely students and various groups so that Indonesian culture can always be maintained and enjoyed in the future